2019
DOI: 10.3390/antiox8090375
|View full text |Cite
|
Sign up to set email alerts
|

Polydatin Encapsulated Poly [Lactic-co-glycolic acid] Nanoformulation Counteract the 7,12-Dimethylbenz[a] Anthracene Mediated Experimental Carcinogenesis through the Inhibition of Cell Proliferation

Abstract: In the present study, the authors have attempted to fabricate Polydatin encapsulated Poly [lactic-co-glycolic acid] (POL-PLGA-NPs) to counteract 7,12-dimethyl benzyl anthracene (DMBA) promoted buccal pouch carcinogenesis in experimental animals. The bio-formulated POL-PLGA-NPs were characterized by dynamic light scattering (DLS), Fourier transform infrared (FTIR) spectroscopy, X-ray powder diffraction (XRD) pattern analysis, and transmission electron microscope (TEM). In addition, the nano-chemopreventive pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 53 publications
1
13
0
Order By: Relevance
“…Figure 2 shows the recorded FTIR spectra, normalized according to the intensity of the absorption band at 1755 cm −1 (C=O stretching carbonate ring), of samples exposed to plasma for 30, 40, 50, 70 and 90 runs. Increasing the exposition time not only led to the decrease in and disappearance of the bands attributed at the allyl groups ( Figure 2 b), but the formation of alkyl backbone could be detected by the appearance of and increase in the plasma exposition time of the absorption bands in the range of 3050–2800 cm −1 , corresponding to C-H stretching, and at 760 cm −1 , related to the rocking vibrations of CH 2 of the long alkyl chains [ 8 , 12 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2 shows the recorded FTIR spectra, normalized according to the intensity of the absorption band at 1755 cm −1 (C=O stretching carbonate ring), of samples exposed to plasma for 30, 40, 50, 70 and 90 runs. Increasing the exposition time not only led to the decrease in and disappearance of the bands attributed at the allyl groups ( Figure 2 b), but the formation of alkyl backbone could be detected by the appearance of and increase in the plasma exposition time of the absorption bands in the range of 3050–2800 cm −1 , corresponding to C-H stretching, and at 760 cm −1 , related to the rocking vibrations of CH 2 of the long alkyl chains [ 8 , 12 , 29 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…The current investigation elucidated that oral treatment of PD-CSNPs, PD and MET reduced lipid peroxidation products and increased the enzymatic antioxidant activity; also exhibited their anti-inflammatory effects and suppressed inflammatory damage in diabetic rats through enhancing expression of Nrf2 and HO-1, which reduces oxidative stress. Notably, polydatin nanoparticles revealed anti-lipid peroxidation and antioxidant activity [45]. Also, PD reduced hyperosmolar stress-induced inflammation by attenuating NF-κβ translocation to the nucleus and the TNF-α mRNA expression [16].…”
Section: Discussionmentioning
confidence: 99%
“…Also, a study to increase cell membrane permeability by encapsulating polydatin was published. They found that polydatin and metformin encapsulated with Poly[lactic-co-glycolic acid] (POL-PLGA-NPs) were to induce a mitochondrial-mediated apoptotic mechanism in vivo [ 39 ]. Therefore, in our results, the reason that a rather high concentration of polydatin induced apoptosis and inhibited metastasis could be inferred that polydatin was not properly absorbed during penetration into the cell membrane.…”
Section: Discussionmentioning
confidence: 99%